Radiation therapy in the era of immune treatment for hepatocellular carcinoma - Chen, Lingjuan; Zhang, Ruiguang; Lin, Zhenyu; Tan, Qiaoyun; Huang, Zhiyong; Liang, Binyong (Frontiers in Immunology, 2023)
Immune checkpoint inhibitors (ICIs) have achieved dramatic advances in recent years and provide new opportunities to treat hepatocellular carcinoma(HCC). To date, several immune checkpoint inhibitors (ICIs) have been approved by FDA for advanced HCC in first-line or second-line therapy. Downstaging conversion therapy for potentially resectable HCC to provide opportunities for surgical intervention is challengable. ICIs have become a hot spot in this field for their high response rate. However, HCC has various etiologies and can evade the immune system through multiple mechanisms, which limit the efficacy of ICI monotherapy and demand novel combination strategies. Radiation therapy (RT) is also a candidate for conversion therapy in HCC, currently gaining increasing attention as a good combination partner with ICIs for its ability to modulate the tumor microenvironment. In this review, we will illustrate the current indications of immunotherapy and radiation, especially in the field of neoadjuvant or conversion therapy. Secondly, we will briefly summarize the current clinical trials in combination therapy and the combination scheme. Finally, we will speculate on predictive biomarkers and future research directions for immunotherapy. This review is hoped to provide references for future research on radiation and immunotherapy to arrive at a promising new era of HCC treatment.